Unpacking the uncertainty construct: Implications for entrepreneurial action - McKelvie, Alexander; Haynie, J. Michael; Gustavsson, Veronica (Journal of Business Venturing, 2011)
Uncertainty is central to entrepreneurship; however robust and generalizable findings that explain the conditions in which uncertainty may impede [or promote] entrepreneurial action remain elusive. We operationalize uncertainty as a multi-dimensional construct composed of state, effect, and response types of uncertainty (Milliken, 1987) to investigate the relationship between uncertainty and entrepreneurial action. We decompose more than 2800 exploitation decision policies nested within a sample of new product decision-makers working in entrepreneurial software firms. We focus on the primary decision-maker's willingness to exploit a given opportunity in the face of varying combinations and manifestations of uncertainty and find that the type of uncertainty experienced influences the willingness to engage in entrepreneurial action differently. Further, we find that differences in how each type of uncertainty is manifested in the environment, the scale of exploitation (i.e. large vs. small), and the entrepreneur's expertise serve to moderate the relationship between uncertainty and action in counter-intuitive ways. We discuss the implications for both theory and practice.